SPATIAL ANALYSIS OF THE DISTRIBUTION OF HOUSEHOLD WASTE CONTAINERS USING GEOGRAPHIC INFORMATION SYSTEMS (GIS). A CASE STUDY OF THE CITY OF AIN EL BEIDA - Dahdouh Fatima; Djakjak Abderraziq; Berkani Fatima zohra; Abdaoui Gihen Rym; Agaguenia Siham; Tabet Ahmed Amine (International Journal of Innovative Technologies in Social Science, 2024)
Urban waste management technology has become one of the most important techniques facing many challenges and concerns in the Algerian city in general and the city of Ain El Beida in particular, due to the quantities of waste produced and constantly increasing, which are due to the increasing population size and consumption rates, which resulted in a set of environmental and health risks and many manifestations of urban degradation due to a lack of appreciation and effectiveness of management, This necessitated study and search for effective solutions with the aim of activating them to improve the process of urban waste management in cities in general. This study aims to clarify how to use geographic information systems (GIS) in the spatial analysis of the distribution of household waste containers in the city of Ain El Beida As a case study and make it more efficient and effective within the urban environment and thus improve its management process. Through this research paper, we have designed interactive maps that provide accurate and comprehensive insights into the distribution of household waste containers in the city of Ain El Beida, which would contribute to directing improvement and effective management efforts with the aim of achieving greater effectiveness and better efficiency in the existing management system. The results also showed that the city’s household waste container distribution system was unbalanced as there was a severe shortage of containers, which affected the overall management system.